Assessing models for estimating future forest biodiversity and ecosystem service provision in support of Integrative Forest Management - Sina Reuter; Verena C. Griess; Jasper M. Fuchs; Volodymyr Trotsiuk; David I. Forrester; Janine Schweier; Olalla Díaz-Yáñez (Ecological Modelling, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

Balancing biodiversity and economics: Using robust Pareto-optimisation to quantify ecological–economic trade-offs in German mixed beech forests - Julia Klenke; Volker von Groß; Jasper M. Fuchs; Larissa R. Topanotti; Benjamin Wildermuth; Carmen Alicia Rivera Pérez; Jing-Zhong Lu; Likulunga Emmanuel Likulunga; Thomas Knoke; Carola Paul (Ambio, 2026)
Biodiversity loss threatens forest ecosystem stability and functioning, while measures to enhance biodiversity trade-off with economic performance. Native tree-species mixtures are promoted to support associated taxa but usually underperform economically compared to non-native species, both in pure and admixed stands. Quantifying ecological–economic trade-offs remains challenging due to uncertainties in economic and biodiversity indicators. Using empirical data on economic (land rent/annuity) and biodiversity indicators (species richness) of five forest taxa from Central German forests, we applied multicriteria optimisation to forest stand-type compositions. We assess the compositional shift of pure (beech, spruce, Douglas-fir) and mixed stand types (beech–spruce, beech–Douglas-fir) under increasing biodiversity targets, accounting for uncertain indicator provision. Stand-type portfolios became more diversified with increasing biodiversity targets. Biodiversity-economic trade-offs were efficiently reduced by incorporating Douglas-fir (in pure and mixed stands) into the portfolio. However, enhancing biodiversity created economic loss, underscoring the need for financial compensation schemes.

The grapevine Vitis shuttleworthii accession D’Arpa reveals resistance against Xiphinema index in an inoculation screening assay - F. Fuchs; J. Schurig; M. Nicklas; A. Baßler; O. Trapp; P. Winterhagen (European Journal of Plant Pathology, 2026)
The Grapevine fanleaf virus (GFLV) transmitted by the vector nematode Xiphinema index causes severe losses in viticulture. Truly resistant rootstocks that inhibit nematode development and virus transmission to grapevines are not available. Seedlings with genetic background of the accession Vitis shuttleworthii D’Arpa were evaluated using an established screening system to test for nematode resistance. For all tested candidate grapevines it turned out that reproduction and fertility of X. index was strongly reduced compared to the susceptible control rootstock Selektion Oppenheim (SO4) and similar to the partly resistant reference rootstock Nemadex Alain Bouquet. GFLV infection was identified on controls and references after inoculation with viruliferous nematodes, but virus was not detected in any of the candidate genotypes with D’Arpa background. Results indicate that D’Arpa contains resistance traits, which may be interesting for breeding nematode resistant rootstocks.

Toxic food: commercial bear meat products are highly contaminated with lead (Pb) from hunting ammunition - Jon M. Arnemo; Adam F. G. Leontowich; Boris Fuchs; Helle B. Hydeskov; Ilia Rodushkin; Samantha Totoni; Cora Paulukat; Jordan O. Hampton (Exposure and Health, 2026)

How useful are outcrop samples to constrain subsurface thermal properties for geothermal exploration? Case study from the Chester formation, UK - Maëlle Brémaud; Neil M. Burnside; Zoe K. Shipton; Claire Bossennec; Sven Fuchs; Fiorenza Deon (Geothermics, 2026)

Experimental study on the interaction of falling films and sprays during cleaning - M. Joppa; R. Schade; T. Hanisch; C. Golla; E. Fuchs; M. Mauermann (Food and Bioproducts Processing, 2026)

Quaternary terrace formation in response to climate, regional uplift and local normal faulting: The Danube terrace staircase of Vienna - B.C. Salcher; S.M. Neuhuber; J.-C. Otto; T. Payer; C. Lüthgens; S. Fuchs; A. Flores-Orozco; J. Nørgaard; S. Grupe; O. Marchhart; A. Wieser; J. Lachner; et al. (Quaternary Science Reviews, 2026)

Per- and Polyfluoroalkyl Substance (PFAS) Levels in Human Plasma Samples Originating from Four Regions with Known Environmental Pollution Compared To Four Nearby Control Regions in Bavaria - Bettina Aschenbrenner; Mandy Wöckner; Veronika Fuchs; Lorena M. Cursino Hron; Caroline Herr; Wolfgang Schober; Dennis Nowak; Matthias Graw; Stefanie Heinze; Wolfgang Völkel (Exposure and Health, 2026)

Innovative cleaning system with movable cavitation nozzle based on the hunting behaviour of the pistol shrimp - R. Murcek; E. Fuchs; J.F. Mauer; M. Finster; M. Mauermann (Food and Bioproducts Processing, 2026)

Correction: Seasonal and Interannual Variability of Exchange between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)

Seasonal and Interannual Variability of Exchange Between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)
This study of Delaware Bay, USA, uses a numerical particle tracking model to examine the exchange of material between the bay and adjacent continental shelf on seasonal timescales. Vertically averaged, near-bottom, and near-surface transport were targeted by simulating particles with three different types of behavior: neutrally buoyant, bottom-seeking (similar to silt settling), and surface-seeking (similar to the slow rise of buoyant material), respectively. Particle release locations are drawn from a space-filling distribution throughout the model domain, and the origin regions of particles that enter the bay vary seasonally, interannually, and with particle behavior. The mean along-shelf circulation is from the northeast to the southwest, and particles entering the bay tend to come from the northeast, within tens of kilometers from shore. Source regions of bottom-seeking particles that enter the bay are farther offshore than source regions of neutral or surface-seeking particles. Bottom-seeking particles also remain in the bay for longer times than particles with other behaviors. Particles of all behaviors are flushed out of Delaware Bay more quickly in winter than in summer. Although this study focuses on a specific region of eastern North America, the findings about sources of particles to the bay are likely applicable to other embayments with similar shelf circulation patterns and may guide efforts to better understand transport of pollutants, larvae, and other material.

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Plankton communities today and tomorrow—potential impacts of multiple global change drivers and marine heatwaves - Cédric L. Meunier; Josefin Schmidt; Antonia Ahme; Areti Balkoni; Katharina Berg; Lea Blum; Maarten Boersma; Jan D. Brüwer; Bernhard M. Fuchs; Luis Gimenez; Maïté Guignard; Ruben Schulte‐Hillen; et al. (Limnology and Oceanography, 2025)
In the context of global change, marine organisms are subjected not only to gradual changes in abiotic parameters, but also to an increasing number of extreme events, such as heatwaves. However, we still know little about the influence of heatwaves on the structure of marine communities, and experimental studies are needed to test the impact of heatwaves alone and in combination with other environmental drivers. Here, we conducted a mesocosm experiment to assess the potential impact of heatwaves on plankton communities, which we did under ambient and future environmental conditions. To simulate future environmental conditions, we simultaneously manipulated temperature and pH based on IPCC predictions for 2100, and dissolved N : P ratios based on the conditions expected in European coastal zones. While we did not observe any effects of simulated heatwaves on phytoplankton abundances, we identified that future environmental conditions may favor smaller phytoplankton species and that additional heatwaves may especially favor small phytoflagellates and coccolithophores. We also observed that future environmental conditions may reduce the abundances and modify the species composition of bacterioplankton, microzooplankton, and mesozooplankton, and that heatwaves may exacerbate these effects. Using a unique approach to examine the potential impacts of heatwaves under current and future environmental conditions on a natural multi‐trophic marine plankton community, we show that the combination of multiple global change drivers has the potential to perturb the entire basis of marine food webs.

Didesmethylrocaglamide cytotoxic activity in high grade serous ovarian cancer in preclinical in vitro and in vivo models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghornb James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Didesmethylrocaglamide Cytotoxic Activity in High Grade Serous Ovarian Cancer in Preclinical In Vitro and In Vivo Models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghorn; James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Morphology of the digestive tract of larvae of Galleria mellonella, An invertebrate model for infections with enteropathogenic bacteria - M. Liebler-Tenorio; P.-A. Saenger; M. Fuchs (Journal of Comparative Pathology, 2025)

Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Grapevine red blotch virus detection in the vineyard: Leveraging machine learning with VIS/NIR hyperspectral images for asymptomatic and symptomatic vines - E. Laroche-Pinel; K. Singh; M. Flasco; M.L. Cooper; M. Fuchs; L. Brillante (Computers and Electronics in Agriculture, 2025)

Lead concentration in blood of Asian black bears in two areas of Central Japan - Koji Yamazaki; Mayumi Ishizuka; Shouta M.M. Nakayama; Nelly Banda; Shinsuke Koike; Yusuke Goto; Kozo Yamazaki; Yui Nemoto; Boris Fuchs; Jon M. Arnemo (Science of The Total Environment, 2025)

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Untangling the Complexity of Climate Change Effects on Plant Reproductive Traits and Pollinators: A Systematic Global Synthesis - Silvana Martén‐Rodríguez; Edson Jacob Cristobal‐Pérez; Martín Hesajim de Santiago‐Hernández; Guillermo Huerta‐Ramos; Lucero Clemente‐Martínez; Gary Krupnick; Orley Taylor; Martha Lopezaraiza‐Mikel; Francisco Javier Balvino‐Olvera; Eugenia M. Sentíes‐Aguilar; Sergio Díaz‐Infante; Armando Aguirre Jaimes; et al. (Global Change Biology, 2025)
Climate change is expected to affect the morphological, physiological, and life‐history traits of plants and animal pollinators due to more frequent extreme heat and other altered weather patterns. This systematic literature review evaluates the effects of climate change on plant and pollinator traits on a global scale to determine how species responses vary among Earth's ecosystems, climate variables, taxonomic groups, and organismal traits. We compiled studies conducted under natural or experimental conditions (excluding agricultural species) and analyzed species response patterns for each trait (advance vs. delay or no change for phenology, decrease vs. increase or no change for other traits). Climate change has advanced plant and animal phenologies across most Earth's biomes, but evidence for temporal plant–pollinator mismatches remains limited. Flower production and plant reproductive success showed diverse responses to warming and low water availability in Alpine and Temperate ecosystems, and a trend for increased or neutral responses in Arctic and Tropical biomes. Nectar rewards mainly experienced negative effects under warming and drought across Alpine and Temperate biomes, but scent emissions increased or changed in composition. Life form (woody vs. nonwoody species) did not significantly influence trait response patterns to climate change. Pollinator fecundity, size, life‐history, developmental, and physiological traits mostly declined with warming across biomes; however, animal abundance and resource acquisition traits showed diverse responses. This review identified critical knowledge gaps that limit our understanding of the impacts of climate change, particularly in tropical/subtropical biomes and southern latitudes. It also highlights the urgent need to sample across a greater range of plant families and pollinator taxa (e.g., beetles, wasps, vertebrates). The diversity of climate change effects should be assessed in the context of other anthropogenic drivers of global change that threaten critically important pollination interactions.

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Monitoring of per- and polyfluoroalkyl substances (PFAS) in human blood samples collected in three regions with known PFAS releases in the environment and three control regions in South Germany - Lorena M. Cursino Hron; Mandy Wöckner; Veronika Fuchs; Ludwig Fembacher; Bettina Aschenbrenner; Caroline Herr; Wolfgang Schober; Stefanie Heinze; Wolfgang Völkel (Archives of Toxicology, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Immunophenotype investigation in feline intestinal non-B-cell lymphoma - Birgitt Wolfesberger; Gabriele Gradner; Barbara C. Rütgen; Katharina M. Hittmair; Ingrid Walter; Taryn A. Donovan; Miriam Kleiter; Alexander Krischak; Iwan A. Burgener; Andrea Fuchs-Baumgartinger (Journal of Comparative Pathology, 2024)

The Associations Between Neuropsychiatric Symptoms and Cognition in People with Dementia: A Systematic Review and Meta-Analysis - Julieta Sabates; Wei-Hsuan Chiu; Samantha Loi; Amit Lampit; Hanna M. Gavelin; Terence Chong; Nathalie Launder; Anita M. Y. Goh; Amy Brodtmann; Nicola Lautenschlager; Alex Bahar-Fuchs (Neuropsychology Review, 2024)
Most people with dementia experience neuropsychiatric symptoms (NPS), including anxiety, depression or disinhibition. There is growing interest in the relationship between NPS and cognitive impairment, but data is still limited. This study aimed to investigate the specific associations between NPS and cognition in people with dementia. MEDLINE, EMBASE and PsycINFO were searched for published, peer-reviewed studies of associations between at least one NPS and one cognitive ability in people with dementia. The quality of the studies was assessed with the NIH National Heart, Lung and Blood Institute’s quality assessment tools. A meta-analysis was conducted using Robumeta package for R. Ninety studies were included. We found significant associations between NPS, global cognition and cognitive domains, e.g. apathy was associated with global cognitive and memory impairment; dysphoria was associated with worse attention; delusions with executive dysfunction. Increased NPS in people with dementia are associated with worse cognitive performance. There were few studies looking at associations between some neuropsychiatric clusters and cognitive abilities, and there was little research on causal relationships. Our review was limited by the inclusion of studies that reported associations in specific formats, and most included people with a diagnosis of Alzheimer’s disease (AD). However, given the large number of studies, this is unlikely to have biased results. More research is needed that includes diverse people with different dementia syndromes. Registration: PROSPERO 2020 CRD42020165565.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

When colors mislead: Genomics and bioacoustics prompt re-classification of Asian flycatcher radiation (Aves: Niltavinae) - Kritika M. Garg; Chyi Yin Gwee; Balaji Chattopadhyay; Nathaniel S. Ng; Dewi M. Prawiradilaga; Gabriel David; Jérôme Fuchs; Hung Le Manh; Jonathan Martinez; Urban Olsson; Vuong Tan Tu; Sophea Chhin; et al. (Molecular Phylogenetics and Evolution, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Toxic elements in arctic and sub-arctic brown bears: Blood concentrations of As, Cd, Hg and Pb in relation to diet, age, and human footprint - Boris Fuchs; Kyle Joly; Grant V. Hilderbrand; Alina L. Evans; Ilia Rodushkin; Lindsey S. Mangipane; Buck A. Mangipane; David D. Gustine; Andreas Zedrosser; Ludovick Brown; Jon M. Arnemo (Environmental Research, 2023)

Phylogeography and distribution modelling reveal the history and future of a saproxylic beetle of European conservation concern - Katarzyna Sikora; Krzysztof Zając; Agnieszka Bieniek; Tomasz Jaworski; Marcin Kadej; Radosław Plewa; Jerzy M. Gutowski; Rafał Ruta; Adrian Smolis; Andreas Eckelt; Teresa Bonacci; Pietro Brandmayr; et al. (Journal of Biogeography, 2023)
Aim The biogeography of European forests presents many interesting case studies, as inferred from phylogeography, contemporary population genetics, and distribution modelling of saproxylic species. Here, we pose four main hypotheses: (i) the phylogeographic paradigm known for temperate species in Europe is also applicable for saproxylic taxa; (ii) current expansion is occurring only in some genetic lineages; (iii) genetic diversity decreases from east to west, reflecting differences in forest naturalness and management; and (iv) climatic changes will force a northward range shift. Location Europe. Taxon The saproxylic beetle, Cucujus cinnaberinus (Scopoli, 1763). Methods Beetles from 37 locations throughout the species range were genotyped using microsatellites and mtDNA (468 and 237 individuals, respectively). Molecular data were analysed to describe population diversity, structure, and demography. 200 records were used to model distribution based on climate data. Results mtDNA analyses revealed three clades: the most divergent in Italy and two less distinct in north‐western and central‐to‐southeastern Europe. Microsatellites showed no clear geographic distribution pattern except for a distinct lineage in Italy. The highest genetic diversity was found in southern refugia, in natural forests of Central‐Eastern Europe, and in a mixing zone in Pannonia. During the Holocene, the Italian population declined, whereas populations in the rest of Europe showed no clear changes. Distribution models revealed the existence of glacial refugia along the coasts of the Adriatic and Black Seas, and northward dispersal in the Holocene continued in the XXI century. Conclusions C. cinnaberinus has a complex historical biogeography, discordant with patterns known for temperate or boreal taxa. The current expansion occurs only in populations from mainland Europe, whereas southernmost populations are in decline. Current genetic diversity is shaped by recent forest management, which is the least intensive in Eastern Europe. Climate change will most likely enhance northward dispersal and threaten the survival of the southernmost populations.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.

A rationale for considering heart/brain axis control in neuropsychiatric disease - Lillian Garrett; Dietrich Trümbach; Nadine Spielmann; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Sabine M. Hölter (Mammalian Genome, 2023)
Neuropsychiatric diseases (NPD) represent a significant global disease burden necessitating innovative approaches to pathogenic understanding, biomarker identification and therapeutic strategy. Emerging evidence implicates heart/brain axis malfunction in NPD etiology, particularly via the autonomic nervous system (ANS) and brain central autonomic network (CAN) interaction. This heart/brain inter-relationship harbors potentially novel NPD diagnosis and treatment avenues. Nevertheless, the lack of multidisciplinary clinical approaches as well as a limited appreciation of molecular underpinnings has stymied progress. Large-scale preclinical multi-systemic functional data can therefore provide supplementary insight into CAN and ANS interaction. We here present an overview of the heart/brain axis in NPD and establish a unique rationale for utilizing a preclinical cardiovascular disease risk gene set to glean insights into heart/brain axis control in NPD. With a top-down approach focusing on genes influencing electrocardiogram ANS function, we combined hierarchical clustering of corresponding regional CAN expression data and functional enrichment analysis to reveal known and novel molecular insights into CAN and NPD. Through ‘support vector machine’ inquiries for classification and literature validation, we further pinpointed the top 32 genes highly expressed in CAN brain structures altering both heart rate/heart rate variability (HRV) and behavior. Our observations underscore the potential of HRV/hyperactivity behavior as endophenotypes for multimodal disease biomarker identification to index aberrant executive brain functioning with relevance for NPD. This work heralds the potential of large-scale preclinical functional genetic data for understanding CAN/ANS control and introduces a stepwise design leveraging preclinical data to unearth novel heart/brain axis control genes in NPD.

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Lead exposure in brown bears is linked to environmental levels and the distribution of moose kills - Ludovick Brown; Boris Fuchs; Jon M. Arnemo; Jonas Kindberg; Ilia Rodushkin; Andreas Zedrosser; Fanie Pelletier (Science of The Total Environment, 2023)

Influences of brood-dependent behavioral variation on blue crab (Callinectes sapidus) larval transport in a wind-driven estuarine plume - Joseph C. Caracappa; Daphne M. Munroe; Heidi L. Fuchs; Robert J. Chant (Ecological Modelling, 2023)

Determining seasonal recharge, storage changes, and specific yield using repeat microgravity and water-level measurements in the Mesilla Basin alluvial aquifer, New Mexico, 2016–2018 - Andrew J. Robertson; Jeffrey R. Kennedy; Libby M. Wildermuth; Meghan T. Bell; Erek H. Fuchs; Alex Rinehart; Irene Fernald (Journal of Applied Geophysics, 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Correction to: Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Simple and robust multiple shoot regeneration and root induction cycle from different explants of Hypericum perforatum L. genotypes - Beena M. Ravindran; Paride Rizzo; Katrin Franke; Jörg Fuchs; John D’Auria (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Hypericum perforatum L. commonly known as Saint John’s Wort (SJW) is an economically important medicinal plant known for accumulating its valuable bioactive compounds in a compartmentalized fashion. The dark glands are very rich in hypericin, and translucent glands are filled with hyperforin. The antibiotic properties of the afore mentioned bioactive compounds make it hard to establish tissue regeneration protocols essential to put in place a transformation platform that is required for testing gene function in this challenging species. In this study, we report the establishment of a regeneration and root induction cycle from different types of explants. The regeneration cycle was set up for the continuous supply of roots and leaf explants for downstream transformation experiments. The most effective medium to obtain multiple shoot-buds from node cultures was MS (Murashige and Skoog, Physiol Plant 15:473–497, 1962) medium supplemented with 0.5 mg L −1 6-Benzylaminopurine (BAP) and 0.5 mg L −1 indole-3-butyric acid (IBA). The same combination yielded copious amounts of shoots from root and leaf explants as well. For rooting the elongated shoots, MS medium devoid of plant growth regulators (PGRs) was sufficient. Nevertheless, addition of a low amount of IBA improved the quantity and quality of roots induced. Additionally, the roots obtained on a medium containing IBA readily developed shoot buds.

Genome‐wide SNPs confirm plumage polymorphism and hybridisation within a Cyornis flycatcher species complex - Elize Y. X. Ng; Siqi Li; Dezhi Zhang; Kritika M. Garg; Gang Song; Jonathan Martinez; Le Manh Hung; Vuong Tan Tu; Jérôme Fuchs; Lu Dong; Urban Olsson; Yuan Huang; et al. (Zoologica Scripta, 2023)
Morphology has been a leading taxonomic guiding light to systematists for the last couple of hundred years. However, the genetic and – more recently – genomic revolution have produced numerous demonstrations of erroneous classifications that were based on labile morphological traits. We used thousands of genome‐wide markers to shed light on evolutionary dynamics in a confusing and taxonomically obscure group of Asian Cyornis flycatchers. Using genomic data, we corroborated recent findings based on three mitochrondrial and five nuclear genes that the two taxa hainanus and klossi which were previously treated as separate species ( Cyornis hainanus and Cyornis rubeculoides klossi , respectively) are genomically homogeneous and form a single species, C. hainanus . We also uncovered a novel case of interbreeding between C. hainanus and a non‐sister species, C. glaucicomans , illustrating these flycatchers' ability to hybridise in marginal situations even after substantial times of divergence. Our study illustrates how genome‐wide loci can shed light on complicated taxonomic problems, resulting in a better integration of phenotypic and genotypic data.

Strong seasonal differences of bacterial polysaccharide utilization in the North Sea over an annual cycle - Greta Giljan; Carol Arnosti; Inga V. Kirstein; Rudolf Amann; Bernhard M. Fuchs (Environmental Microbiology, 2022)
Summary Marine heterotrophic bacteria contribute considerably to global carbon cycling, in part by utilizing phytoplankton‐derived polysaccharides. The patterns and rates of two different polysaccharide utilization modes – extracellular hydrolysis and selfish uptake – have previously been found to change during spring phytoplankton bloom events. Here we investigated seasonal changes in bacterial utilization of three polysaccharides, laminarin, xylan and chondroitin sulfate. Strong seasonal differences were apparent in mode and speed of polysaccharide utilization, as well as in bacterial community compositions. Compared to the winter month of February, during the spring bloom in May, polysaccharide utilization was detected earlier in the incubations and a higher portion of all bacteria took up laminarin selfishly. Highest polysaccharide utilization was measured in June and September, mediated by bacterial communities that were significantly different from spring assemblages. Extensive selfish laminarin uptake, for example, was detectible within a few hours in June, while extracellular hydrolysis of chondroitin was dominant in September. In addition to the well‐known Bacteroidota and Gammaproteobacteria clades, the numerically minor verrucomicrobial clade Pedosphaeraceae could be identified as a rapid laminarin utilizer. In summary, polysaccharide utilization proved highly variable over the seasons, both in mode and speed, and also by the bacterial clades involved.

Knowledge, Attitudes, Willingness to Pay, and Patient Preferences About Genetic Testing and Subsequent Risk Management for Cancer Prevention - Fangjian Guo; Jacqueline M. Hirth; Erika L. Fuchs; Leslie E. Cofie; Veronica Brown; Yong-Fang Kuo; Maria E. Fernandez; Abbey B. Berenson (Journal of Cancer Education, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Journal Club - Andreas Peschel; Andreas Diepold; Thilo M. Fuchs; Julia Ast; Marion Lemoine; Bernhard Schink; Kürşad Turgay; Bärbel Stecher; Kai Thormann; Remy Colin; Johannes Sander; Petra Neumann-Staubitz; et al. (BIOspektrum, 2022)

Degrading permafrost river catchments and their impact on Arctic Ocean nearshore processes - Paul J. Mann; Jens Strauss; Juri Palmtag; Kelsey Dowdy; Olga Ogneva; Matthias Fuchs; Michael Bedington; Ricardo Torres; Luca Polimene; Paul Overduin; Gesine Mollenhauer; Guido Grosse; et al. (Ambio, 2022)
Arctic warming is causing ancient perennially frozen ground (permafrost) to thaw, resulting in ground collapse, and reshaping of landscapes. This threatens Arctic peoples' infrastructure, cultural sites, and land-based natural resources. Terrestrial permafrost thaw and ongoing intensification of hydrological cycles also enhance the amount and alter the type of organic carbon (OC) delivered from land to Arctic nearshore environments. These changes may affect coastal processes, food web dynamics and marine resources on which many traditional ways of life rely. Here, we examine how future projected increases in runoff and permafrost thaw from two permafrost-dominated Siberian watersheds—the Kolyma and Lena, may alter carbon turnover rates and OC distributions through river networks. We demonstrate that the unique composition of terrestrial permafrost-derived OC can cause significant increases to aquatic carbon degradation rates (20 to 60% faster rates with 1% permafrost OC). We compile results on aquatic OC degradation and examine how strengthening Arctic hydrological cycles may increase the connectivity between terrestrial landscapes and receiving nearshore ecosystems, with potential ramifications for coastal carbon budgets and ecosystem structure. To address the future challenges Arctic coastal communities will face, we argue that it will become essential to consider how nearshore ecosystems will respond to changing coastal inputs and identify how these may affect the resiliency and availability of essential food resources.

Metagenomic analysis of nepoviruses: diversity, evolution and identification of a genome region in members of subgroup A that appears to be important for host range - J. M. Hily; N. Poulicard; J. Kubina; J. S. Reynard; A. S. Spilmont; M. Fuchs; O. Lemaire; E. Vigne (Archives of Virology, 2021)
Data mining and metagenomic analysis of 277 open reading frame sequences of bipartite RNA viruses of the genus Nepovirus , family Secoviridae , were performed, documenting how challenging it can be to unequivocally assign a virus to a particular species, especially those in subgroups A and C, based on some of the currently adopted taxonomic demarcation criteria. This work suggests a possible need for their amendment to accommodate pangenome information. In addition, we revealed a host-dependent structure of arabis mosaic virus (ArMV) populations at a cladistic level and confirmed a phylogeographic structure of grapevine fanleaf virus (GFLV) populations. We also identified new putative recombination events in members of subgroups A, B and C. The evolutionary specificity of some capsid regions of ArMV and GFLV that were described previously and biologically validated as determinants of nematode transmission was circumscribed in silico . Furthermore, a C-terminal segment of the RNA-dependent RNA polymerase of members of subgroup A was predicted to be a putative host range determinant based on statistically supported higher π (substitutions per site) values for GFLV and ArMV isolates infecting Vitis spp. compared with non- Vitis -infecting ArMV isolates. This study illustrates how sequence information obtained via high-throughput sequencing can increase our understanding of mechanisms that modulate virus diversity and evolution and create new opportunities for advancing studies on the biology of economically important plant viruses.

Designing real-world laboratories for sustainable urban transformation: addressing ambiguous roles and expectations in transdisciplinary teams - Sandra Huning; C. Räuchle; M. Fuchs (Sustainability Science, 2021)
This paper reflects upon the potential of real-world laboratories (RWLs) to promote sustainable urban development. RWLs strive for knowledge production through collective action in experimental settings. Their implementation in urban studies faces two major challenges: (1) the ambiguity of roles university researchers need to fill, and (2) the variety of expectations among team members from different institutional backgrounds. Based on research in one trans-European and three German RWLs, we propose a stronger focus on team development to help researchers in RWLs address these challenges more systematically. In particular, this means support in terms of resources and infrastructure (time, space, and training). We argue that the improvement of RWL team performance has great impact on the potentials of RWLs in transformative urban studies. Thus, the article contributes to the ongoing debate on the city as a laboratory and site of experimentation in times of multiple crises.

Complex interactions with nutrients and sediment alter the effects of predation on a reef‐building coral - Mallory M. Rice; Daniel G. Baldwin; Janine N. Fischer; Corinne Fuchs; Deron E. Burkepile (Marine Ecology, 2021)
Framework‐building corals create the three‐dimensional structure of coral reefs and are subject to predation from fishes, echinoderms, and gastropods. Anthropogenic stressors can magnify the effects of such top‐down pressure on foundation species. The gastropod Coralliophila violacea (Kiener, 1836) depletes coral energy reserves via predation, potentially increasing coral susceptibility to land‐based pollution (i.e., sediment accumulation and nutrient pollution). We hypothesized that sedimentation would worsen coral mortality, while nutrient enrichment would mitigate the harmful effects of sediment and predation on coral mortality by increasing the densities of algal symbionts. To test these hypotheses, we conducted in situ surveys of the fringing reefs in Mo'orea, French Polynesia to explore the relationships among massive Porites spp . cover, C. violacea densities, and sediment accumulation on coral colonies across low and high nutrient sites. We also conducted a factorial field experiment to test the interactions among these stressors on coral tissue mortality, symbiont densities, and chlorophyll. Massive Porites colonies at higher nutrient sites had C. violacea densities 13 times higher than at low nutrient sites but there was no difference in the amount of live tissue on coral colonies with or without snails among these sites. In our experiment, there were interactions between predation and nutrients as well as nutrients and sediment that impacted coral mortality. Sedimentation and predation by C. violacea increased coral tissue mortality independently by ~20%. Nutrient enrichment reduced this effect in corals under sedimentation or predation pressure by lowering coral tissue mortality by 18% and increasing algal symbiont densities by ~28%. Our results indicate that sediment does not magnify top‐down pressure on this coral, and that moderate nutrient enrichment may interact with predation in complex, unexpected ways to alter the responses of corals to top‐down pressure.

Endogenous anandamide and self-reported pain are significantly reduced after a 2-week multimodal treatment with and without radon therapy in patients with knee osteoarthritis: a pilot study - M. Gaisberger; J. Fuchs; M. Riedl; S. Edtinger; R. Reischl; G. Grasmann; B. Hölzl; F. Landauer; H. Dobias; F. Eckstein; M. Offenbächer; M. Ritter; et al. (International Journal of Biometeorology, 2021)
Multimodal therapies comprising spa applications are widely used as non-pharmaceutical treatment options for musculoskeletal diseases. The purpose of this randomized, controlled, open pilot study was to elucidate the involvement of the endocannabinoid system in a multimodal therapy approach. Twenty-five elderly patients with knee osteoarthritis (OA) received a 2-week spa therapy with or without combination of low-dose radon therapy in the Bad Gastein radon gallery. A 10-point numerical rating scale (pain in motion and at rest), WOMAC questionnaire, and the EuroQol-5D (EQ-5D) questionnaire were recorded at baseline, and during treatment period at weeks one and two, and at 3-month and 6-month follow-ups. Plasma levels of the endocannabinoid anandamide (AEA) were determined at baseline and at 2 weeks, and serum levels of several cartilage metabolism markers at all five time-points. A significant and sustained reduction of self-reported knee pain was observed in the study population, but no further significant effect of the additional radon therapy up and above base therapy. This pain reduction was accompanied by a significant reduction of AEA plasma levels during treatment in both groups. No significant differences were seen in serum marker concentrations between the groups treated with or without radon, but a small reduction of serum cartilage degradation markers was observed during treatment in both groups. This is the first study investigating AEA levels in the context of a non-pharmacological OA treatment. Since the endocannabinoid system represents a potential target for the development of new therapeutics, further studies will have to elucidate its involvement in OA pain.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

Full Parameterisation Matters for the Best Performance of Crop Models: Inter-comparison of a Simple and a Detailed Maize Model - A. M. Manschadi; J. Eitzinger; M. Breisch; W. Fuchs; T. Neubauer; A. Soltani (International Journal of Plant Production, 2021)
Process-based crop growth models have become indispensable tools for investigating the effects of genetic, management, and environmental factors on crop productivity. One source of uncertainty in crop model predictions is model parameterization, i.e. estimating the values of model input parameters, which is carried out very differently by crop modellers. One simple (SSM-iCrop) and one detailed (APSIM) maize ( Zea mays L.) model were partially or fully parameterized using observed data from a 2-year field experiment conducted in 2016 and 2017 at the UFT (Universitäts- und Forschungszentrum Tulln, BOKU) in Austria. Model initialisation was identical for both models based on field measurements. Partial parameterization (ParLevel_1) was first performed by estimating only those parameters related to crop phenology. Full parameterization (ParLevel_2) was then conducted by estimating parameters related to phenology plus those affecting dry mass production and partitioning, nitrogen uptake, and grain yield formation. With ParLevel_1, both models failed to provide accurate estimation of LAI, dry mass accumulation, nitrogen uptake and grain yield, but the performance of APSIM was generally better than SSM-iCrop. Full parameterization greatly improved the performance of both crop models, but it was more effective for the simple model, so that SSM-iCrop was equally well or even better compared to APSIM. It was concluded that full parameterization is indispensable for improving the accuracy of crop model predictions regardless whether they are simple or detailed. Simple models seem to be more vulnerable to incomplete parameterization, but they better respond to full parameterization. This needs confirmation by further research.

Evaluation of two rapid antigen tests to detect SARS-CoV-2 in a hospital setting - Andreas Osterman; Hanna-Mari Baldauf; Marwa Eletreby; Jochen M. Wettengel; Suliman Q. Afridi; Thimo Fuchs; Elena Holzmann; Anton Maier; Johanna Döring; Natascha Grzimek-Koschewa; Maximilian Muenchhoff; Ulrike Protzer; et al. (Medical Microbiology and Immunology, 2021)
Successful containment strategies for the SARS-CoV-2 pandemic will depend on reliable diagnostic assays. Point-of-care antigen tests (POCT) may provide an alternative to time-consuming PCR tests to rapidly screen for acute infections on site. Here, we evaluated two SARS-CoV-2 antigen tests: the STANDARD™ F COVID-19 Ag FIA (FIA) and the SARS-CoV-2 Rapid Antigen Test (RAT). For diagnostic assessment, we used a large set of PCR-positive and PCR-negative respiratory swabs from asymptomatic and symptomatic patients and health care workers in the setting of two University Hospitals in Munich, Germany, i.e. emergency rooms, patient care units or employee test centers. For FIA, overall clinical sensitivity and specificity were 45.4% ( n = 381) and 97.8% ( n = 360), respectively, and for RAT, 50.3% ( n = 445) and 97.7% ( n = 386), respectively. For primary diagnosis of asymptomatic and symptomatic individuals, diagnostic sensitivities were 60.9% (FIA) ( n = 189) and 64.5% (RAT) ( n = 256). This questions these tests’ utility for the reliable detection of acute SARS-CoV-2-infected individuals, in particular in high-risk settings. We support the proposal that convincing high-quality outcome data on the impact of false-negative and false-positive antigen test results need to be obtained in a POCT setting. Moreover, the efficacy of alternative testing strategies to complement PCR assays must be evaluated by independent laboratories, prior to widespread implementation in national and international test strategies.

Short‐term changes in polysaccharide utilization mechanisms of marine bacterioplankton during a spring phytoplankton bloom - Greta Reintjes; Bernhard M. Fuchs; Mirco Scharfe; Karen H. Wiltshire; Rudolf Amann; Carol Arnosti (Environmental Microbiology, 2020)
Summary Spring phytoplankton blooms in temperate environments contribute disproportionately to global marine productivity. Bloom‐derived organic matter, much of it occurring as polysaccharides, fuels biogeochemical cycles driven by interacting autotrophic and heterotrophic communities. We tracked changes in the mode of polysaccharide utilization by heterotrophic bacteria during the course of a diatom‐dominated bloom in the German Bight, North Sea. Polysaccharides can be taken up in a ‘selfish’ mode, where initial hydrolysis is coupled to transport into the periplasm, such that little to no low‐molecular weight (LMW) products are externally released to the environment. Alternatively, polysaccharides hydrolyzed by cell‐surface attached or free extracellular enzymes (external hydrolysis) yield LMW products available to the wider bacterioplankton community. In the early bloom phase, selfish activity was accompanied by low extracellular hydrolysis rates of a few polysaccharides. As the bloom progressed, selfish uptake increased markedly, and external hydrolysis rates increased, but only for a limited range of substrates. The late bloom phase was characterized by high external hydrolysis rates of a broad range of polysaccharides and reduced selfish uptake of polysaccharides, except for laminarin. Substrate utilization mode is related both to substrate structural complexity and to the bloom‐stage dependent composition of the heterotrophic bacterial community.

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

MDH1 deficiency is a metabolic disorder of the malate–aspartate shuttle associated with early onset severe encephalopathy - Melissa H. Broeks; Hanan E. Shamseldin; Amal Alhashem; Mais Hashem; Firdous Abdulwahab; Tarfa Alshedi; Iman Alobaid; Fried Zwartkruis; Denise Westland; Sabine Fuchs; Nanda M. Verhoeven-Duif; Judith J. M. Jans; et al. (Human Genetics, 2019)

Gene flow and genetic admixture across a secondary contact zone between two divergent lineages of the Eurasian Green Woodpecker Picus viridis - J.-M. Pons; C. Masson; G. Olioso; J. Fuchs (Journal of Ornithology, 2019)

Influence of genetic variation in the vitamin D pathway on plasma 25-hydroxyvitamin D3 levels and survival among patients with metastatic colorectal cancer - Chen Yuan; Lindsay Renfro; Pratibha B. Ambadwar; Fang-Shu Ou; Howard L. McLeod; Federico Innocenti; Jeffrey A. Meyerhardt; Brian M. Wolpin; Richard M. Goldberg; Axel Grothey; Charles S. Fuchs; Kimmie Ng (Cancer Causes & Control, 2019)

Crybb2 Mutations Consistently Affect Schizophrenia Endophenotypes in Mice - Tamara Heermann; Lillian Garrett; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Jochen Graw; Sabine M. Hölter (Molecular Neurobiology, 2019)

Bewertung von Talsperren-Erhöhungsoptionen in der Schweiz - Helge Fuchs; David Felix; Michelle Müller-Hagmann; Robert M. Boes (WASSERWIRTSCHAFT, 2019)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Metabolic versatility of a novel N 2 ‐fixing Alphaproteobacterium isolated from a marine oxygen minimum zone - Clara Martínez‐Pérez; Wiebke Mohr; Anne Schwedt; Julia Dürschlag; Cameron M. Callbeck; Harald Schunck; Julien Dekaezemacker; Caroline R. T. Buckner; Gaute Lavik; Bernhard M. Fuchs; Marcel M. M. Kuypers (Environmental Microbiology, 2018)
Summary The N 2 ‐fixing (diazotrophic) community in marine ecosystems is dominated by non‐cyanobacterial microorganisms. Yet, very little is known about their identity, function and ecological relevance due to a lack of cultured representatives. Here we report a novel heterotrophic diazotroph isolated from the oxygen minimum zone (OMZ) off Peru. The new species belongs to the genus Sagittula ( Rhodobacteraceae , Alphaproteobacteria ) and its capability to fix N 2 was confirmed in laboratory experiments. Genome sequencing revealed that it is a strict heterotroph with a high versatility in substrate utilization and energy acquisition mechanisms. Pathways for sulfide oxidation and nitrite reduction to nitrous oxide are encoded in the genome and might explain the presence throughout the Peruvian OMZ. The genome further indicates that this novel organism could be in direct interaction with other microbes or particles. NanoSIMS analyses were used to compare the metabolic potential of S. castanea with single‐cell activity in situ ; however, N 2 fixation by this diazotroph could not be detected at the isolation site. While the biogeochemical impact of S. castanea is yet to be resolved, its abundance and widespread distribution suggests that its potential to contribute to the marine N input could be significant at a larger geographical scale.

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Influence of immunostimulant polysaccharides, nucleic acids, and Bacillus strains on the innate immune and acute stress response in turbots (Scophthalmus maximus) fed soy bean- and wheat-based diets - V. I. Fuchs; J. Schmidt; M. J. Slater; B. H. Buck; D. Steinhagen (Fish Physiology and Biochemistry, 2017)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide - Gottfried Wilharm; Evelyn Skiebe; Paul G. Higgins; Marie T. Poppel; Ulrike Blaschke; Sarah Leser; Christine Heider; Magdalena Heindorf; Paul Brauner; Udo Jäckel; Karin Böhland; Christiane Cuny; et al. (Environmental Microbiology, 2017)
Summary The natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A . baumannii . We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A . baumannii from 3% of sampled chicken ( n = 220), 8% of geese ( n = 40) and 25% of white stork nestlings ( n = 661). Virulence of selected avian A . baumannii isolates was comparable to that of clinical isolates in the Galleria mellonella infection model. Whole genome sequencing revealed the close relationship of an antibiotic‐susceptible chicken isolate from Germany with a multidrug‐resistant human clinical isolate from China and additional linkages between livestock isolates and human clinical isolates related to international clonal lineages. Moreover, we identified stork isolates related to human clinical isolates from the United States. Multilocus sequence typing disclosed further kinship between avian and human isolates. Avian isolates do not form a distinct clade within the phylogeny of A . baumannii , instead they diverge into different lineages. Further, we provide evidence that A . baumannii is constantly present in the habitats occupied by storks. Collectively, our study suggests A . baumannii could be a zoonotic organism that may disseminate into livestock.

Role of the agranular insular cortex in contextual control over cocaine-seeking behavior in rats - Amy A. Arguello; Rong Wang; Carey M. Lyons; Jessica A. Higginbotham; Matthew A. Hodges; Rita A. Fuchs (Psychopharmacology, 2017)

Genomic and physiological analyses of ‘ Reinekea forsetii ’ reveal a versatile opportunistic lifestyle during spring algae blooms - Burak Avcı; Richard L. Hahnke; Meghan Chafee; Tanja Fischer; Harald Gruber‐Vodicka; Halina E. Tegetmeyer; Jens Harder; Bernhard M. Fuchs; Rudolf I. Amann; Hanno Teeling (Environmental Microbiology, 2017)
Summary Gammaproteobacterial Reinekea spp. were detected during North Sea spring algae blooms in the years 2009‐2012, with relative abundances of up to 16% in the bacterioplankton. Here, we explore the ecophysiology of ‘R. forsetii' strain Hel1_31_D35 that was isolated during the 2010 spring bloom using (i) its manually annotated, high‐quality closed genome, (ii) re‐analysis of in situ data from the 2009–2012 blooms and (iii) physiological tests. High resolution analysis of 16S rRNA gene sequences suggested that ‘R. forsetii' dominated Reinekea populations during these blooms. This was corroborated by retrieval of almost complete Hel1_31_D35 genomes from 2009 and 2010 bacterioplankton metagenomes. Strain Hel1_31_D35 can use numerous low‐molecular weight substrates including diverse sugar monomers, and few but relevant algal polysaccharides such as mannan, α‐glucans, and likely bacterial peptidoglycan. It oxidizes thiosulfate to sulfate, and ferments under anoxic conditions. The strain can attach to algae and thrives at low phosphate concentrations as they occur during blooms. Its genome encodes RTX toxin and secretion proteins, and in cultivation experiments Hel1_31_D35 crude cell extracts inhibited growth of a North Sea Polaribacter strain. Our data suggest that the combination of these traits make strain Hel1_31_D35 a versatile opportunist that is particularly competitive during spring phytoplankton blooms.

Direct‐geneFISH: a simplified protocol for the simultaneous detection and quantification of genes and rRNA in microorganisms - Jimena Barrero‐Canosa; Cristina Moraru; Laura Zeugner; Bernhard M. Fuchs; Rudolf Amann (Environmental Microbiology, 2017)
Summary Although fluorescence in situ hybridization (FISH) with specific ribosomal RNA (rRNA)‐targeted oligonucleotides is a standard method to detect and identify microorganisms, the specific detection of genes in bacteria and archaea, for example by using geneFISH, requires complicated and lengthy (> 30 h) procedures. Here we report a much improved protocol, direct‐geneFISH, which allows specific gene and rRNA detection within less than 6 h. For direct‐geneFISH, catalyzed amplification reporter deposition (CARD) steps are removed and fluorochrome‐labelled polynucleotide gene probes and rRNA‐targeted oligonucleotide probes are hybridized simultaneously. The protocol allows quantification of gene copy numbers per cell and the signal of the directly labelled probes enables a subcellular localization of the rRNA and target gene. The detection efficiencies of direct‐geneFISH were first evaluated on Escherichia coli carrying the target gene on a copy‐control vector. We could show that gene copy numbers correlated to the geneFISH signal within the cells. The new protocol was then applied for the detection of the sulfate thiolhydrolase ( soxB ) genes in cells of the gammaproteobacterial clade SUP05 in Lake Rogoznica, Croatia. Cell and gene detection efficiencies by direct‐geneFISH were statistically identical to those obtained with the original geneFISH, demonstrating the suitability of the simpler and faster protocol for environmental samples.

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

Influence of the Po River runoff on the bacterioplankton community along trophic and salinity gradients in the Northern Adriatic Sea - Ilaria Pizzetti; Giuliano Lupini; Fabrizio Bernardi Aubry; Francesco Acri; Bernhard M. Fuchs; Stefano Fazi (Marine Ecology, 2016)
The Po River runoff strongly affects the oceanographic and ecological characteristics of the Northern Adriatic Sea. Catalysed reported deposition ‐ fluorescence in situ hybridization ( CARD ‐ FISH ) analysis was employed to assess how the composition of the coastal bacterioplankton community is influenced by the river runoff in two different seasons (spring and autumn). Samples were collected from the water column along a coastal–offshore transect in the Northern Adriatic Sea at different depths. Four clone libraries were then constructed from coastal (0 m) and offshore waters (−65 m). Higher abundances of bacteria were recorded in coastal waters as compared with the offshore samples. This result was mainly due to the trophic state of the water column, and it was related to salinity. Particularly, Actinobacteria and Gammaproteobacteria were affected by the riverine inputs, whereas Bacteroidetes and Alphaproteobacteria showed only minor responses. This was particularly clear in the autumn sample, in which a clear difference between the coastal and the offshore samples was found due to a strong influence of the less saline river water with high nutrient concentrations. Analysis of 205 partial length 16S rRNA gene sequences indicated a high diversity with the dominance of Alphaproteobacteria , Bacteroidetes and Gammaproteobacteria mainly affiliated to coastal and marine bacterioplankton clades. Actinobacteria were also detected and, together with Gammaproteobacteria , strongly follow the freshwater intrusion. Overall, our results indicate that the seasonal difference in the Po River discharge greatly affects the bacterioplankton community. In spring we observed a smooth transition from coastal to open‐sea conditions owing to the more superficial freshwater plume. In autumn the deeper freshwater intrusion in the coastal site and thermal stratification offshore resulted in a marked difference between the coastal and offshore microbial communities.

Polysaccharide utilisation loci of Bacteroidetes from two contrasting open ocean sites in the North Atlantic - Christin M. Bennke; Karen Krüger; Lennart Kappelmann; Sixing Huang; Angélique Gobet; Margarete Schüler; Valérie Barbe; Bernhard M. Fuchs; Gurvan Michel; Hanno Teeling; Rudolf I. Amann (Environmental Microbiology, 2016)
Summary Marine Bacteroidetes have pronounced capabilities of degrading high molecular weight organic matter such as proteins and polysaccharides. Previously we reported on 76 Bacteroidetes ‐affiliated fosmids from the North Atlantic Ocean's boreal polar and oligotrophic subtropical provinces. Here, we report on the analysis of further 174 fosmids from the same libraries. The combined, re‐assembled dataset (226 contigs; 8.8 Mbp) suggests that planktonic Bacteroidetes at the oligotrophic southern station use more peptides and bacterial and animal polysaccharides, whereas Bacteroidetes at the polar station (East‐Greenland Current) use more algal and plant polysaccharides. The latter agrees with higher abundances of algae and terrigenous organic matter, including plant material, at the polar station. Results were corroborated by in‐depth bioinformatic analysis of 14 polysaccharide utilisation loci from both stations, suggesting laminarin‐specificity for four and specificity for sulfated xylans for two loci. In addition, one locus from the polar station supported use of non‐sulfated xylans and mannans, possibly of plant origin. While peptides likely represent a prime source of carbon for Bacteroidetes in open oceans, our data suggest that as yet unstudied clades of these Bacteroidetes have a surprisingly broad capacity for polysaccharide degradation. In particular, laminarin‐specific PULs seem widespread and thus must be regarded as globally important.

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Chlamydial seasonal dynamics and isolation of ‘ C andidatus N eptunochlamydia vexilliferae’ from a T yrrhenian coastal lake - Ilaria Pizzetti; Frederik Schulz; Tomáš Tyml; Bernhard M. Fuchs; Rudolf Amann; Matthias Horn; Stefano Fazi (Environmental Microbiology, 2016)
Summary The C hlamydiae are a phylum of obligate intracellular bacteria comprising important human and animal pathogens, yet their occurrence in the environment, their phylogenetic diversity and their host range has been largely underestimated. We investigated the seasonality of environmental chlamydiae in a Tyrrhenian coastal lake. By catalysed reporter deposition fluorescence in situ hybridization, we quantified the small planktonic cells and detected a peak in the abundance of environmental chlamydiae in early autumn with up to 5.9 × 10 4 cells ml −1 . Super‐resolution microscopy improved the visualization and quantification of these bacteria and enabled the detection of pleomorphic chlamydial cells in their protist host directly in an environmental sample. To isolate environmental chlamydiae together with their host, we applied a high‐throughput limited dilution approach and successfully recovered a V exillifera sp., strain harbouring chlamydiae (93% 16 S r RNA sequence identity to S imkania negevensis ), tentatively named ‘ C andidatus N eptunochlamydia vexilliferae’. Transmission electron microscopy in combination with fluorescence in situ hybridization was used to prove the intracellular location of these bacteria representing the first strain of marine chlamydiae stably maintained alongside with their host in a laboratory culture. Taken together, this study contributes to a better understanding of the distribution and diversity of environmental chlamydiae in previously neglected marine environments.

Assessing the influence of historic net and gross land changes on the carbon fluxes of Europe - Richard Fuchs; Catharina J. E. Schulp; Geerten M. Hengeveld; Peter H. Verburg; Jan G. P. W. Clevers; Mart‐Jan Schelhaas; Martin Herold (Global Change Biology, 2016)
Legacy effects of land cover/use on carbon fluxes require considering both present and past land cover/use change dynamics. To assess past land use dynamics, model‐based reconstructions of historic land cover/use are needed. Most historic reconstructions consider only the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). Studies about the impact of gross and net land change accounting methods on the carbon balance are still lacking. In this study, we assessed historic changes in carbon in soils for five land cover/use types and of carbon in above‐ground biomass of forests. The assessment focused on Europe for the period 1950 to 2010 with decadal time steps at 1‐km spatial resolution using a bookkeeping approach. To assess the implications of gross land change data, we also used net land changes for comparison. Main contributors to carbon sequestration between 1950 and 2010 were afforestation and cropland abandonment leading to 14.6 PgC sequestered carbon (of which 7.6 PgC was in forest biomass). Sequestration was highest for old‐growth forest areas. A sequestration dip was reached during the 1970s due to changes in forest management practices. Main contributors to carbon emissions were deforestation (1.7 PgC) and stable cropland areas on peaty soils (0.8 PgC). In total, net fluxes summed up to 203 TgC yr −1 (98 TgC yr −1 in forest biomass and 105 TgC yr −1 in soils). For areas that were subject to land changes in both reconstructions (35% of total area), the differences in carbon fluxes were about 68%. Overall for Europe the difference between accounting for either gross or net land changes led to 7% difference (up to 11% per decade) in carbon fluxes with systematically higher fluxes for gross land change data.

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Exome sequencing identifies a nonsense mutation in Fam46a associated with bone abnormalities in a new mouse model for skeletal dysplasia - Susanne Diener; Sieglinde Bayer; Sibylle Sabrautzki; Thomas Wieland; Birgit Mentrup; Gerhard K. H. Przemeck; Birgit Rathkolb; Elisabeth Graf; Wolfgang Hans; Helmut Fuchs; Marion Horsch; Thomas Schwarzmayr; et al. (Mammalian Genome, 2016)

Single-crystal structure and Raman spectroscopy of synthetic titanite analog CaAlSiO4F - Hannes Krüger; Daniel M. Többens; Peter Tropper; Udo Haefeker; Volker Kahlenberg; Martin R. Fuchs; Vincent Olieric; Ulrike Troitzsch (Mineralogy and Petrology, 2015)

Comparison of bacterial communities on limnic versus coastal marine particles reveals profound differences in colonization - Mina Bižić‐Ionescu; Michael Zeder; Danny Ionescu; Sandi Orlić; Bernhard M. Fuchs; Hans‐Peter Grossart; Rudolf Amann (Environmental Microbiology, 2015)
Summary Marine and limnic particles are hotspots of organic matter mineralization significantly affecting biogeochemical element cycling. Fluorescence in‐situ hybridization and pyrosequencing of 16S rRNA genes were combined to investigate bacterial diversity and community composition on limnic and coastal marine particles > 5 and > 10 μm respectively. Limnic particles were more abundant (average: 1 × 10 7 l −1 ), smaller in size (average areas: 471 versus 2050 μm 2 ) and more densely colonized (average densities: 7.3 versus 3.6 cells 100 μm −2 ) than marine ones. Limnic particle‐associated ( PA ) bacteria harboured A lphaproteobacteria and B etaproteobacteria , and unlike previously suggested sizeable populations of G ammaproteobacteria , A ctinobacteria and B acteroidetes . Marine particles were colonized by P lanctomycetes and B etaproteobacteria additionally to A lphaproteobacteria , B acteroidetes and G ammaproteobacteria . Large differences in individual particle colonization could be detected. High‐throughput sequencing revealed a significant overlap of PA and free‐living ( FL ) bacteria highlighting an underestimated connectivity between both fractions. PA bacteria were in 14/21 cases more diverse than FL bacteria, reflecting a high heterogeneity in the particle microenvironment. We propose that a ratio of Chao 1 indices of PA / FL PA communities of both environments differ substantially.

Dilution cultivation of marine heterotrophic bacteria abundant after a spring phytoplankton bloom in the N orth S ea - Richard L. Hahnke; Christin M. Bennke; Bernhard M. Fuchs; Alexander J. Mann; Erhard Rhiel; Hanno Teeling; Rudolf Amann; Jens Harder (Environmental Microbiology, 2015)
Summary The roles of individual bacterioplankton species in the re‐mineralization of algal biomass are poorly understood. Evidence from molecular data had indicated that a spring diatom bloom in the G erman B ight of the N orth S ea in 2009 was followed by a rapid succession of uncultivated bacterioplankton species, including members of the genera U lvibacter , F ormosa , P olaribacter (class F lavobacteria ) and R einekea (class G ammaproteobacteria) . We isolated strains from the same site during the diatom bloom in spring 2010 using dilution cultivation in an artificial seawater medium with micromolar substrate and nutrient concentrations. Flow cytometry demonstrated growth from single cells to densities of 10 4 –10 6 cells ml –1 and a culturability of 35%. Novel F ormosa , P olaribacter and R einekea strains were isolated and had 16 S r RNA gene sequence identities of > 99.8% with bacterioplankton in spring or summer 2009. Genomes of selected isolates were draft sequenced and used for read recruitment of metagenomes from bacterioplankton in 2009. Metagenome reads covered 93% of a F ormosa clade B , 91% of a R einekea and 74% of a F ormosa clade A genome, applying a ≥ 94.5% nucleotide identity threshold. These novel strains represent abundant bacterioplankton species thriving on coastal phytoplankton blooms in the N orth S ea.

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis - Vishwadeep Ahluwalia; James B. Wade; Douglas M. Heuman; Thomas A. Hammeke; Arun J. Sanyal; Richard K. Sterling; R. Todd Stravitz; Velimir Luketic; Mohammad S. Siddiqui; Puneet Puri; Michael Fuchs; Micheal J. Lennon; et al. (Metabolic Brain Disease, 2014)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

Distribution of a consortium between unicellular algae and the N 2 fixing cyanobacterium UCYN ‐ A in the North Atlantic Ocean - Andreas Krupke; Gaute Lavik; Hannah Halm; Bernhard M. Fuchs; Rudolf I. Amann; Marcel M. M. Kuypers (Environmental Microbiology, 2014)
Summary The globally abundant, uncultured unicellular cyanobacterium UCYN ‐ A was recently discovered living in association with a eukaryotic cell closely related to a prymnesiophyte. Here, we established a double CAtalysed Reporter Deposition‐Fluorescence In Situ Hybridization ( CARD ‐ FISH ) approach to identify both partners and provided quantitative information on their distribution and abundance across distinct water masses along a transect in the N orth A tlantic O cean. The N 2 fixation activity coincided with the detection of UCYN ‐ A cells and was only observed in oligotrophic ( μ M and μ M ) and warm (> 18° C ) surface waters. Parallel 16 S ribosomal RNA gene analyses among unicellular diazotrophs indicated that only UCYN ‐ A cells were present. UCYN ‐ A cells were associated with an algal partner or non‐associated using the double CARD ‐ FISH approach. We demonstrated that UCYN ‐A cells living in association with H aptophyta were the dominant form (87.0 ± 6.1%), whereas non‐associated UCYN ‐ A cells represented only a minor fraction (5.2 ± 3.9%). Interestingly, UCYN ‐ A cells were also detected living in association with unknown single‐celled eukaryotes in small amounts (7.8 ± 5.2%), presumably A lveolata. The proposed ecological niche of UCYN ‐ A as an oligotrophic, mesophilic and obligate symbiotic nitrogen‐fixing microorganism is evident for the N orth A tlantic O cean.

Involvement of amygdalar protein kinase A, but not calcium/calmodulin-dependent protein kinase II, in the reconsolidation of cocaine-related contextual memories in rats - Amy A. Arguello; Matthew A. Hodges; Audrey M. Wells; Honorio Lara; Xiaohu Xie; Rita A. Fuchs (Psychopharmacology, 2014)

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

An additional substrate binding site in a bacterial phenylalanine hydroxylase - Judith A. Ronau; Lake N. Paul; Julian E. Fuchs; Isaac R. Corn; Kyle T. Wagner; Klaus R. Liedl; Mahdi M. Abu-Omar; Chittaranjan Das (European Biophysics Journal, 2013)

Holocene river and slope activity in the Visoko Basin, Bosnia‐ H erzegovina – climate and land‐use effects - S. DREIBRODT; C. LUBOS; R. HOFMANN; N. MÜLLER‐SCHEEßEL; I. RICHLING; O. NELLE; M. FUCHS; K. RASSMANN; Z. KUJUNDŽIĆ‐VEJZAGIĆ; H.‐R. BORK; J. MÜLLER (Journal of Quaternary Science, 2013)
Alluvial and colluvial deposits were investigated at prehistoric tells close to the Bosna River. The chronology is based on ten radiocarbon ages, five optically stimulated luminescence ages, and on the archaeological record. Fluvial activity of the Bosna River is indicated by overbank fines [ca. 5000 (±1000) BC , 500 BC until today] and a phase of lateral displacement of the river bed with subsequent channel fills ca. 2000–500 BC . Early Holocene fluvial activity was probably triggered by climatic variability but might have promoted the expansion of Neolithic societies into the Visoko Basin. Mid‐ to late Holocene river activity occurred under increased climatic aridity but coincided with the expansion of prehistoric settlements to a wider area of the river basin on hard rocks in the adjacent mountainous areas. The destruction of the thin soil cover in the mountains is discussed as a probable trigger for enduring subsequent river activity. This is also indicated by a change in the geochemical signature of the alluvial sediments. The proposed mechanism might explain the mid to late Holocene river history in other regions. The potential of geochemical analyses and diachronous high‐resolution archaeological records to make inferences regarding sediment sources and geomorphological processes is demonstrated. Copyright © 2013 John Wiley & Sons, Ltd.

Clone libraries and single cell genome amplification reveal extended diversity of uncultivated magnetotactic bacteria from marine and freshwater environments - Sebastian Kolinko; Gerhard Wanner; Emanuel Katzmann; Felizitas Kiemer; Bernhard M. Fuchs; Dirk Schüler (Environmental Microbiology, 2013)
Summary Magnetotactic bacteria ( MTB ), which orient along the earth's magnetic field using magnetosomes, are ubiquitous and abundant in marine and freshwater environments. Previous phylogenetic analysis of diverse MTB has been limited to few cultured species and the most abundant and conspicuous members of natural populations, which were assigned to various lineages of the P roteobacteria , the N itrospirae phylum as well as the candidate division OP 3. However, their known phylogenetic diversity still not matches the large morphological and ultrastructural variability of uncultured MTB found in environmental communities. Here, we used analysis of 16 S rRNA gene clone libraries in combination with microsorting and whole‐genome amplification to systematically address the entire diversity of uncultured MTB from two different habitats. This approach revealed extensive and novel diversity of MTB within the freshwater and marine sediment samples. In total, single‐cell analysis identified eight different phylotypes, which were only partly represented in the clone libraries, and which could be unambiguously assigned to their respective morphotypes. Identified MTB belonged to the A lphaproteobacteria (seven species) and the N itrospirae phylum (two species). End‐sequencing of a small insert library created from WGA ‐derived DNA of a novel conspicuous magnetotactic vibrio identified genes with highest similarity to two cultivated MTB as well as to other phylogenetic groups. In conclusion, the combination of metagenomic cloning and single cell sorting represents a powerful approach to recover maximum bacterial diversity including low‐abundant magnetotactic phylotypes from environmental samples and also provides access to genomic analysis of uncultivated MTB .

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Role of nicotinic acetylcholine receptors in the effects of cocaine-paired contextual stimuli on impulsive decision making in rats - Xiaohu Xie; Amy A. Arguello; Andrew M. Reittinger; Audrey M. Wells; Rita A. Fuchs (Psychopharmacology, 2012)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Mathias Schlegel; Lukáš Radosa; Ulrike M. Rosenfeld; Sabrina Schmidt; Cornelia Triebenbacher; Paul-Walter Löhr; Dieter Fuchs; Marta Heroldová; Eva Jánová; Michal Stanko; Ladislav Mošanský; Jana Fričová; et al. (Virus Genes, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genomic content of uncultured Bacteroidetes from contrasting oceanic provinces in the North Atlantic Ocean - Paola R. Gómez‐Pereira; Margarete Schüler; Bernhard M. Fuchs; Christin Bennke; Hanno Teeling; Jost Waldmann; Michael Richter; Valérie Barbe; Elodie Bataille; Frank Oliver Glöckner; Rudolf Amann (Environmental Microbiology, 2012)
Summary Bacteroidetes are widespread in marine systems where they play a crucial role in organic matter degradation. Whole genome analysis of several strains has revealed a broad glycolytic and proteolytic potential. In this study, we used a targeted metagenomic approach to investigate the degradation capabilities of distinct Bacteroidetes clades from two contrasting regions of the North Atlantic Ocean, the Polar Biome (BPLR) and the North Atlantic Subtropical (NAST). We present here the analysis of 76 Bacteroidetes fosmids, of which 28 encode the 16S rRNA gene as phylogenetic marker, and their comparison to complete Bacteroidetes genomes. Almost all of the 16S rRNA harbouring fosmids belonged to clades that we previously identified in BPLR and NAST. The majority of sequenced fosmids could be assigned to Bacteroidetes affiliated with the class Flavobacteria . We also present novel genomic information on the classes Cytophagia and Sphingobacteria , suggesting a capability of the latter for attachment to algal surfaces. In our fosmid set we identified a larger potential for polysaccharide degradation and cell surface attachment in the phytoplankton‐rich BPLR. Particularly, two flavobacterial fosmids, one affiliated with the genus Polaribacter , showed a whole armoury of enzymes that likely function in degradation of sulfated polysaccharides known to be major constituents of phytoplankton cell walls. Genes involved in protein and peptidoglycan degradation, although present in both fosmid sets, seemed to have a slight preponderance in NAST. This study provides support for the hypothesis of a distinct specialization among marine Bacteroidetes for the degradation of certain types of polymers.

Generation and characterization of koi herpesvirus recombinants lacking viral enzymes of nucleotide metabolism - Walter Fuchs; Dieter Fichtner; Sven M. Bergmann; Thomas C. Mettenleiter (Archives of Virology, 2011)

In vitro testing for anti-inflammatory properties of compounds employing peripheral blood mononuclear cells freshly isolated from healthy donors - M. Jenny; M. Klieber; D. Zaknun; S. Schroecksnadel; K. Kurz; M. Ledochowski; H. Schennach; Dietmar Fuchs (Inflammation Research, 2011)

Morphology, testes development and behaviour of unusual triploid males in microchromosome‐carrying clones of Poecilia formosa - D. K. Lamatsch; M. Stöck; R. Fuchs; M. Döbler; R. Wacker; J. Parzefall; I. Schlupp; M. Schartl (Journal of Fish Biology, 2010)
In a microchromosome‐carrying laboratory stock of the normally all‐female Amazon molly Poecilia formosa triploid individuals were obtained, all of which spontaneously developed into males. A comparison of morphology of the external and internal insemination apparatus and the gonads, sperm ploidy and behaviour, to laboratory‐bred F 1 hybrids revealed that the triploid P. formosa males, though producing mostly aneuploid sperm, are partly functional males that differ mainly in sperm maturation and sexual motivation from gonochoristic P. formosa males.

GeneFISH – an in situ technique for linking gene presence and cell identity in environmental microorganisms - Cristina Moraru; Phyllis Lam; Bernhard M. Fuchs; Marcel M. M. Kuypers; Rudolf Amann (Environmental Microbiology, 2010)
Summary Our knowledge concerning the metabolic potentials of as yet to be cultured microorganisms has increased tremendously with the advance of sequencing technologies and the consequent discoveries of novel genes. On the other hand, it is often difficult to reliably assign a particular gene to a phylogenetic clade, because these sequences are usually found on genomic fragments that carry no direct marker of cell identity, such as rRNA genes. Therefore, the aim of the present study was to develop geneFISH – a protocol for linking gene presence with cell identity in environmental samples, the signals of which can be visualized at a single cell level. This protocol combines rRNA‐targeted catalysed reporter deposition – fluorescence in situ hybridization and in situ gene detection. To test the protocol, it was applied to seawater samples from the Benguela upwelling system. For gene detection, a polynucleotide probe mix was used, which was designed based on crenarchaeotal amo A clone libraries prepared from each seawater sample. Each probe in the mix was selected to bind to targets with up to 5% mismatches. To determine the hybridization parameters, the T m of probes, targets and hybrids was estimated based on theoretical calculations and in vitro measurements. It was shown that at least 30%, but potentially the majority of the Crenarchaeota present in these samples harboured the amo A gene and were therefore likely to be catalysing the oxidation of ammonia.

Morphological and biological characterization of cell line developed from bovine Echinococcus granulosus - Claudia I. Echeverría; Dora M. Isolabella; Elio A. Prieto Gonzalez; Araceli Leonardelli; Laura Prada; Alina Perrone; Alicia G. Fuchs (In Vitro Cellular & Developmental Biology - Animal, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Latitudinal distribution of prokaryotic picoplankton populations in the Atlantic Ocean - Martha Schattenhofer; Bernhard M. Fuchs; Rudolf Amann; Mikhail V. Zubkov; Glen A. Tarran; Jakob Pernthaler (Environmental Microbiology, 2009)
Summary Members of the prokaryotic picoplankton are the main drivers of the biogeochemical cycles over large areas of the world's oceans. In order to ascertain changes in picoplankton composition in the euphotic and twilight zones at an ocean basin scale we determined the distribution of 11 marine bacterial and archaeal phyla in three different water layers along a transect across the Atlantic Ocean from South Africa (32.9°S) to the UK (46.4°N) during boreal spring. Depth profiles down to 500 m at 65 stations were analysed by catalysed reporter deposition fluorescence in situ hybridization (CARD‐FISH) and automated epifluorescence microscopy. There was no obvious overall difference in microbial community composition between the surface water layer and the deep chlorophyll maximum (DCM) layer. There were, however, significant differences between the two photic water layers and the mesopelagic zone. SAR11 (35 ± 9%) and Prochlorococcus (12 ± 8%) together dominated the surface waters, whereas SAR11 and Crenarchaeota of the marine group I formed equal proportions of the picoplankton community below the DCM (both ∼15%). However, due to their small cell sizes Crenarchaeota contributed distinctly less to total microbial biomass than SAR11 in this mesopelagic water layer. Bacteria from the uncultured Chloroflexi ‐related clade SAR202 occurred preferentially below the DCM (4–6%). Distinct latitudinal distribution patterns were found both in the photic zone and in the mesopelagic waters: in the photic zone, SAR11 was more abundant in the Northern Atlantic Ocean (up to 45%) than in the Southern Atlantic gyre (∼25%), the biomass of Prochlorococcus peaked in the tropical Atlantic Ocean, and Bacteroidetes and Gammaproteobacteria bloomed in the nutrient‐rich northern temperate waters and in the Benguela upwelling. In mesopelagic waters, higher proportions of SAR202 were present in both central gyre regions, whereas Crenarchaeota were clearly more abundant in the upwelling regions and in higher latitudes. Other phylogenetic groups such as the Planctomycetes , marine group II Euryarchaeota and the uncultured clades SAR406, SAR324 and SAR86 rarely exceeded more than 5% of relative abundance.

Evidence for distinct populations of human Merkel cells - A.-C. Eispert; F. Fuchs; J. M. Brandner; P. Houdek; E. Wladykowski; Ingrid Moll (Histochemistry and Cell Biology, 2009)

Chemical composition of tourmaline from the Asarcık Pb–Zn–Cu ± U deposit, Şebinkarahisar, Turkey - F. Yavuz; Y. Fuchs; N. Karakaya; M. Ç. Karakaya (Mineralogy and Petrology, 2008)

A microdiversity study of anammox bacteria reveals a novel Candidatus Scalindua phylotype in marine oxygen minimum zones - Dagmar Woebken; Phyllis Lam; Marcel M. M. Kuypers; S. Wajih A. Naqvi; Boran Kartal; Marc Strous; Mike S. M. Jetten; Bernhard M. Fuchs; Rudolf Amann (Environmental Microbiology, 2008)
Summary The anaerobic oxidation of ammonium (anammox) contributes significantly to the global loss of fixed nitrogen and is carried out by a deep branching monophyletic group of bacteria within the phylum Planctomycetes . Various studies have implicated anammox to be the most important process responsible for the nitrogen loss in the marine oxygen minimum zones (OMZs) with a low diversity of marine anammox bacteria. This comprehensive study investigated the anammox bacteria in the suboxic zone of the Black Sea and in three major OMZs (off Namibia, Peru and in the Arabian Sea). The diversity and population composition of anammox bacteria were investigated by both, the 16S rRNA gene sequences and the 16S‐23S rRNA internal transcribed spacer (ITS). Our results showed that the anammox bacterial sequences of the investigated samples were all closely related to the Candidatus Scalindua genus. However, a greater microdiversity of marine anammox bacteria than previously assumed was observed. Both phylogenetic markers supported the classification of all sequences in two distinct anammox bacterial phylotypes: Candidatus Scalindua clades 1 and 2. Scalindua 1 could be further divided into four distinct clusters, all comprised of sequences from either the Namibian or the Peruvian OMZ. Scalindua 2 consisted of sequences from the Arabian Sea and the Peruvian OMZ and included one previously published 16S rRNA gene sequence from Lake Tanganyika and one from South China Sea sediment (97.9–99.4% sequence identity). This cluster showed only ≤ 97% sequence identity to other known Candidatus Scalindua species. Based on 16S rRNA gene and ITS sequences we propose that the anammox bacteria of Scalindua clade 2 represent a novel anammox bacterial species, for which the name Candidatus Scalindua arabica is proposed. As sequences of this new cluster were found in the Arabian Sea, the Peruvian OMZ, in Lake Tanganyika and in South China sediment, we assume a global distribution of Candidatus Scalindua arabica as it is observed for Candidatus Scalindua sorokinii/brodae (or Scalindua clade 1).

Multiple interspecies recombination events within RNA2 of Grapevine fanleaf virus and Arabis mosaic virus - E. Vigne; A. Marmonier; M. Fuchs (Archives of Virology, 2008)

Flow cytometric measurements do not reveal different ploidy levels in Minthostachys (Lamiaceae) - A. N. Schmidt-Lebuhn; J. Fuchs; M. Kessler (Plant Systematics and Evolution, 2008)

Improvement and application of the biocontrol fungus Stagonospora convolvuli LA39 formulation for efficient control of Calystegia sepium and Convolvulus arvensis - D. Boss; E. Schläpfer; J. Fuchs; G. Défago; M. Maurhofer (Journal of Plant Diseases and Protection, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microbial control of phosphate in the nutrient‐depleted North Atlantic subtropical gyre - Mikhail V. Zubkov; Isabelle Mary; E. Malcolm S. Woodward; Phillip E. Warwick; Bernhard M. Fuchs; David J. Scanlan; Peter H. Burkill (Environmental Microbiology, 2007)
Summary Little is known about the dynamics of dissolved phosphate in oligotrophic areas of the world's oceans, where concentrations are typically in the nanomolar range. Here, we have budgeted phosphate uptake by the dominant microbial groups in order to assess the effect of the microbial control of this depleted nutrient in the North Atlantic gyre. Low concentrations (2.2 ± 1.2 nM) and rapid microbial uptake (2.1 ± 2.4 nM day −1 ) of bioavailable phosphate were repeatedly determined in surface waters of the North Atlantic oligotrophic gyre during spring and autumn research cruises, using a radiotracer dilution bioassay technique. Upper estimates of the concentration of bioavailable phosphate were 7–55% of the dissolved mineral phosphate suggesting that a considerable part of the chemically measured nanomolar phosphate was in a form unavailable for direct microbial uptake. A 1:1 relationship ( r 2 = 0.96, P Prochlorococcus phototrophic cyanobacteria, were the two major competing groups for bioavailable phosphate. These heterotrophic bacteria had low nucleic acid content and 60% of them comprised of SAR11 clade cells based on the results of fluorescence in situ hybridization. Each of the two competing bacterial groups was responsible for an average of 45% of the phosphate uptake, while Synechococcus cyanobacteria (7%) and picoplanktonic algae (0.3%) played minor roles in direct phosphate uptake. We have demonstrated that phosphate uptake in the oligotrophic gyre is rapid and dominated by two bacterial groups rather than by algae.

Characterization of a naturally occurring recombinant isolate of Grapevine fanleaf virus - E. Vigne; G. Demangeat; V. Komar; M. Fuchs (Archives of Virology, 2005)

Potentiation of cocaine-primed reinstatement of drug seeking in female rats during estrus - Tod E. Kippin; Rita A. Fuchs; Ritu H. Mehta; Jordan M. Case; Macon P. Parker; Heather A. Bimonte-Nelson; Ronald E. See (Psychopharmacology, 2005)

Neuromagnetic motor fields accompanying self-paced rhythmic finger movement at different rates - Justine M. Mayville; Armin Fuchs; J. A. Scott Kelso (Experimental Brain Research, 2005)

Chronic psychosocial stress in tree shrews: effect of the substance P (NK1 receptor) antagonist L-760735 and clomipramine on endocrine and behavioral parameters - Marieke G. C. van der Hart; Gabriel de Biurrun; Boldizsár Czéh; Nadia M. J. Rupniak; Johan A. den Boer; Eberhard Fuchs (Psychopharmacology, 2005)

Cloning and characterization of SK2 channel from chicken short hair cells - TM Matthews; RK Duncan; M Zidanic; TH Michael; PA Fuchs (Journal of Comparative Physiology A, 2005)

Influence of sex and estrous cyclicity on conditioned cue-induced reinstatement of cocaine-seeking behavior in rats - Rita A. Fuchs; K. Allison Evans; Ritu H. Mehta; Jordan M. Case; Ronald E. See (Psychopharmacology, 2005)

Patterns of Iridoid Glycoside Production and Induction in Plantago lanceolata and the Importance of Plant Age - Alexander Fuchs; M. Deane Bowers (Journal of Chemical Ecology, 2004)

Exploring the method of optical dating and comparison of optical and 14 C ages of Late Weichselian coversands in the southern Netherlands - D. Vandenberghe; C. Kasse; S. M. Hossain; F. De Corte; P. Van Den Haute; M. Fuchs; A. S. Murray (Journal of Quaternary Science, 2004)
A study was made of the applicability of three different techniques for equivalent dose ( D e ) determination in the optical dating of quartz: the single‐aliquot regenerative‐dose technique (SAR), the single‐aliquot additive‐dose technique (SAAD) and the multiple‐aliquot additive‐dose technique (MAAD). For this purpose, quartz grains were extracted from a sequence of Upper Pleniglacial to Late‐glacial coversands exposed at the locality of Ossendrecht in the southwestern Netherlands, a site for which both radiocarbon and earlier luminescence dates are available, providing independent age control. Upon testing the different assumptions underlying each of the three OSL techniques investigated, the SAR protocol was found to be the technique of choice. The optical ages obtained with this protocol were in good agreement with the chronostratigraphical position of the sediments investigated and with the available chronostratigraphical information on the same and equivalent deposits. This confirms the suitability of the SAR technique for dating coversands. Furthermore, a small laboratory intercomparison of SAR‐based D e determinations yielded results that were in fair overall agreement. Copyright © 2004 John Wiley & Sons, Ltd.

Die Zahl der „Schmuckknoten“ beim AlpensteinbockCapra i. ibex: Hilfe zur Bestimmung oder Anlass zur Verwirrung? - P. Lüps; B. Dauwalder; R. Fuchs; M. Zuber (European Journal of Wildlife Research, 2003)

Fluorescence in situ hybridization of 16S rRNA gene clones (Clone‐FISH) for probe validation and screening of clone libraries - Andreas Schramm; Bernhard M. Fuchs; Jeppe L. Nielsen; Mauro Tonolla; David A. Stahl (Environmental Microbiology, 2002)
Summary A method is presented for fluorescence in situ hybridization (FISH) of 16S rRNA gene clones targeting in vivo transcribed plasmid inserts (Clone‐FISH). Several different cloning approaches and treatments to generate target‐rRNA in the clones were compared. Highest signal intensities of Clone‐FISH were obtained using plasmids with a T7 RNA polymerase promoter and host cells with an IPTG‐inducible T7 RNA polymerase. Combined IPTG‐induction and chloramphenicol treatment of those clones resulted in FISH signals up to 2.8‐fold higher than signals of FISH with probe EUB338 to cells of Escherichia coli . Probe dissociation curves for three oligonucleotide probes were compared for reference cells containing native (FISH) or cloned (Clone‐FISH) target sequences. Melting behaviour and calculated T d values were virtually identical for clones and cells, providing a format to use 16S rRNA gene clones instead of pure cultures for probe validation and optimization of hybridization conditions. The optimized Clone‐FISH protocol was also used to screen an environmental clone library for insert sequences of interest. In this application format, 13 out of 82 clones examined were identified to contain sulphate‐reducing bacterial rRNA genes. In summary, Clone‐FISH is a simple and fast technique, compatible with a wide variety of cloning vectors and hosts, that should have general utility for probe validation and screening of clone libraries.

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Size and sequence variability of the Arabis mosaic virus protein 2A - T. Wetzel; M. Fuchs; M. Bobko; G. Krczal (Archives of Virology, 2002)

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Linking the composition of bacterioplankton to rapid turnover of dissolved dimethylsulphoniopropionate in an algal bloom in the North Sea - Mikhail V. Zubkov; Bernhard M. Fuchs; Stephen D. Archer; Ronald P. Kiene; Rudolf Amann; Peter H. Burkill (Environmental Microbiology, 2001)
The algal osmolyte, dimethylsulphoniopropionate (DMSP), is abundant in the surface oceans and is the major precursor of dimethyl sulphide (DMS), a gas involved in global climate regulation. Here, we report results from an in situ Lagrangian study that suggests a link between the microbially driven fluxes of dissolved DMSP (DMSPd) and specific members of the bacterioplankton community in a North Sea coccolithophore bloom. The bacterial population in the bloom was dominated by a single species related to the genus Roseobacter , which accounted for 24% of the bacterioplankton numbers and up to 50% of the biomass. The abundance of the Roseobacter cells showed significant paired correlation with DMSPd consumption and bacterioplankton production, whereas abundances of other bacteria did not. Consumed DMSPd (28 nM day −1 ) contributed 95% of the sulphur and up to 15% of the carbon demand of the total bacterial populations, suggesting the importance of DMSP as a substrate for the Roseobacter ‐dominated bacterioplankton. In dominating DMSPd flux, the Roseobacter species may exert a major control on DMS production. DMSPd turnover rate was 10 times that of DMS (2.7 nM day −1 ), indicating that DMSPd was probably the major source of DMS, but that most of the DMSPd was metabolized without DMS production. Our study suggests that single species of bacterioplankton may at times be important in metabolizing DMSP and regulating the generation of DMS in the sea.

Increased blood-brain barrier permeability in neuro-asymptomatic HIV-1-infected individualscorrelation with cerebrospinal fluid HIV-1 RNA and neopterin levels - L M Andersson, L Hagberg, D Fuchs, B (Journal of NeuroVirology, 2001)

Debris removal by head-pushing in A. florea Fabr. honeybees - M. Sen Sarma; S. Fuchs; J. Tautz (The Science of Nature, 2000)

Changes in community composition during dilution cultures of marine bacterioplankton as assessed by flow cytometric and molecular biological techniques - Bernhard M. Fuchs; Mikhail V. Zubkov; Kerstin Sahm; Peter H. Burkill; Rudolf Amann (Environmental Microbiology, 2000)
Dilution cultures are a common technique for measuring the growth of bacterioplankton communities. In this study, the taxonomic composition of marine bacterioplankton dilution cultures was followed in water samples from Plymouth Sound and the English Channel (UK). Bacterial abundances as well as protein and DNA content were closely monitored by flow cytometry. Denaturing gradient gel electrophoresis (DGGE) of polymerase chain reaction (PCR)‐amplified 16S rDNA fragments and fluorescence in situ hybridization (FISH) were applied directly to the water samples and to cells sorted from the dilution cultures based on their protein and DNA content. As expected, a rapid activation of bacteria occurred. However, molecular techniques showed that the community developed in the dilution culture within 1 day was significantly different from that in the original water samples. Whereas in the original samples, cells detectable by FISH were dominated by members of the C ytophaga / Flavobacterium (CF) cluster, in dilution cultures, gamma‐proteobacteria accounted for the majority of cells detected, followed by alpha‐proteobacteria. An actively growing and an apparently non‐growing population with average cellular protein contents of 24 and 4.5 fg respectively, were sorted by flow cytometry. FISH indicated mostly gamma‐ (64%) and alpha‐proteobacteria (33%) in the first active fraction and 78% members of the CF cluster in the second fraction. Sequencing of DGGE bands confirmed the FISH assignments of the latter two groups. The data presented clearly show that even relatively short‐term dilution experiments do not measure in situ growth, but rather growth patterns of an enrichment. Furthermore, it was demonstrated that the combination of flow cytometric analysis and sorting combined with FISH and DGGE analysis presented a fairly rapid method of analysing the taxonomic composition of marine bacterioplankton.

A cross-sectional study of workers in the chemical industry with occupational exposure to hexamethylenetetramine - R. Merget; M. Topcu; K. Friese; R. Vormberg; T. Fuchs; M. Raulf-Heimsoth; R. Breitstadt (International Archives of Occupational and Environmental Health, 1999)

Scales of Heterogeneities in the Continental Crust and Upper Mantle - M. Tittgemeyer; F. Wenzel; T. Ryberg; K. Fuchs (Pure and Applied Geophysics, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Behavioral interactions produced by co-administration of 7-OH-DPAT with cocaine or apomorphine in the rat - Taline V. Khroyan; Rita A. Fuchs; Alex M. Beck; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1999)

Xanthine oxidase inhibition by allopurinol affects the reliability of urinary caffeine metabolic ratios as markers for N -acetyltransferase 2 and CYP1A2 activities - P. Fuchs; W. E. Haefeli; H. R. Ledermann; M. Wenk (European Journal of Clinical Pharmacology, 1999)

Mössbauer and infrared spectrometry of lizardite- 1T from Monte Fico, Elba - Y. Fuchs; J. Linares; M. Mellini (Physics and Chemistry of Minerals, 1998)

A comparison of sequence resolution on plant chromosomes: PRINS versus FISH - M. Menke; J. Fuchs; I. Schubert (Theoretical and Applied Genetics, 1998)

Esterases of Corbicula fluminea as Biomarkers of Exposure to Organophosphorus Pesticides - S. B. Basack; M. L. Oneto; J. S. Fuchs; E. J. Wood; E. M. Kesten (Bulletin of Environmental Contamination and Toxicology, 1998)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)

Differential induction of enzymes involved in anaerobic metabolism of aromatic compounds in the denitrifying bacterium Thauera aromatica - J. Heider; Matthias Boll; Klaus Breese; Sabine Breinig; Christa Ebenau-Jehle; Ulrich Feil; Nasser Gad'on; Diana Laempe; Birgitta Leuthner; M. El-Said Mohamed; Sabine Schneider; Gerhard Burchhardt; et al. (Archives of Microbiology, 1998)

Anaerobic metabolism of l -phenylalanine via benzoyl-CoA in the denitrifying bacterium Thauera aromatica - Sabine Schneider; M. E.-S. Mohamed; G. Fuchs (Archives of Microbiology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Cytogenetics in fruit breeding - localization of ribosomal RNA genes on chromosomes of apple (Malus×domestica Borkh.) - M. Schuster; J. Fuchs; I. Schubert (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identification and transcriptional analysis of pseudorabies virus UL6 to UL12 genes - J. M. Dijkstra; W. Fuchs; T. C. Mettenleiter; B. G. Klupp (Archives of Virology, 1997)

Acetate oxidation to CO2 via a citric acid cycle involving an ATP-citrate lyase: a mechanism for the synthesis of ATP via substrate level phosphorylation in Desulfobacter postgatei growing on acetate and sulfate - D. Mller; R. Schauder; G. Fuchs; R. K. Thauer (Archives of Microbiology, 1987)

Effects of temperature on cadmium toxicity to the green algaScenedesmus acutus. II. Light-limited growth in continuous culture - J. M. van Gemert; H. J. G. ten Hoopen; J. A. Roels; A. Fuchs (Antonie van Leeuwenhoek, 1985)

Bacteria and yeasts as possible candidates for the production of inulinases and levanases - A. Fuchs; J. M. de Bruijn; C. J. Niedeveld (Antonie van Leeuwenhoek, 1985)